Comparison of The Assessment of The Braden Scale and The Gosnell Scale in Assessing The Level of Risk of Pressure Sores in Bed Rest Patients - Marviana Marviana; Ani Astuti; Diah Merdekawati (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2022)
Background: Pressure sores will make the healing process take a long time. Skin care to prevent pressure sores can be started since the patient is identified as being at risk for pressure ulcers through a pressure ulcer risk assessment, a pressure ulcer risk assessment method using two scales, namely the Braden and Gosnell scales. Objectives: This study aims to compare the assessment of the Braden scale and the Gosnell scale in assessing the level of risk of pressure sores in bed rest patients. Methods: This research design uses quantitative with comparative studies. The population is 706 people with a total sample of 61 people by accidental sampling. The research was conducted on 12 August – 25 September 2020. Data were analyzed univariate and bivariate using test Kappa. Results: The results show that most of the risk levels of pressure sores are more with moderate risk as much as 47.5% assessed by the Braden scale. Most of the level of risk of pressure sores is more with a mild risk of 62.3% assessed by the Gosnell scale. The Gosnell scale is better used to measure pressure sores in bed rest patients in the Inpatient Room at Bhayangkara Hospital Jambi in 2020 by showing the Kappa test value of 0.797. Conclusion: The Gosnell scale is better used to measure pressure sores in bed rest patients. It is recommended that the Gosnell test scale be applied in hospitals as an assessment of the risk of pressure sores in bed rest patients.